The Influence of Acceptance Technology Model (TAM) in the use of software by Auditors that implicate in performance - Darmaningtyas, I Gusti Bagus; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2017)
This paper aims to analyze the effect of technology acceptance model (TAM) in the use of software by the auditor and its implications on the performance of auditors (Studies At Public Accounting Firm in Bali Province). This research was conducted in all offices of seven public accounting firms in Bali in 2017 with the number of auditors as many as 73 people with census method. Data collection was done by distributing questionnaires with 60 respondents who returned and 13 were aborted through path analysis techniques. The results of the analysis prove that perceived usefulness and perceived ease of use have a significant positive effect on auditor performance. Perceived usefulness and perceived ease of use have a significant positive effect on behavioral intention to use auditor. Behavioral intention to use is able to mediate the positive influence of perceived usefulness and perceived ease of use on auditor performance at Public Accounting Firm in Bali.